2016
DOI: 10.1371/journal.pone.0151962
|View full text |Cite
|
Sign up to set email alerts
|

Community Attitudes and Practices of Urban Residents Regarding Predation by Pet Cats on Wildlife: An International Comparison

Abstract: International differences in practices and attitudes regarding pet cats' interactions with wildlife were assessed by surveying citizens from at least two cities in Australia, New Zealand, the UK, the USA, China and Japan. Predictions tested were: (i) cat owners would agree less than non-cat owners that cats might threaten wildlife, (ii) cat owners value wildlife less than non-cat owners, (iii) cat owners are less accepting of cat legislation/restrictions than non-owners, and (iv) respondents from regions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 94 publications
(122 reference statements)
12
118
3
1
Order By: Relevance
“…How does this compare with the beliefs of New Zealand cat owners? A survey of 151 cat owners in New Zealand indicated that 95% of companion cats had free access to the outdoors (Farnworth et al 2010a), whereas a recent survey found that New Zealand cat owners had low support for 24-h containment of cats (18.6% of respondents; Hall et al 2016). Further research to identify the drivers and barriers of pet-cat containment is warranted.…”
Section: Business and Marketingmentioning
confidence: 99%
See 3 more Smart Citations
“…How does this compare with the beliefs of New Zealand cat owners? A survey of 151 cat owners in New Zealand indicated that 95% of companion cats had free access to the outdoors (Farnworth et al 2010a), whereas a recent survey found that New Zealand cat owners had low support for 24-h containment of cats (18.6% of respondents; Hall et al 2016). Further research to identify the drivers and barriers of pet-cat containment is warranted.…”
Section: Business and Marketingmentioning
confidence: 99%
“…Therefore, social research to help understand the public perception of cats Hall et al 2016 in New Zealand is vital. Some research has begun (see Table 1), including investigating the use and perception of cat collars (cat owners preferred to use microchips for identification purposes; Harrod et al 2016), to the acceptability of unowned-cat control (respondents who owned cats perceived non-lethal control of unowned cats to be more acceptable than lethal control methods, when compared with non-owners; Farnworth et al 2011).…”
Section: Social Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, cats are one of the most popular companion animals worldwide and have several positive roles in human lifestyles (Hall et al, 2016). Cats comfort people, and interactions with cats, including outdoor ones, relieve people from stress and improve human health (Brickel, 1979;Siegel, 1990;Wood et al, 2007).…”
Section: Introductionmentioning
confidence: 99%